2015
DOI: 10.1016/j.nicl.2014.12.015
|View full text |Cite
|
Sign up to set email alerts
|

Thalamic–hippocampal–prefrontal disruption in relapsing–remitting multiple sclerosis

Abstract: BackgroundCortical, thalamic and hippocampal gray matter atrophy in relapsing–remitting MS (RRMS) is associated cognitive deficits. However, the role of interconnecting white matter pathways including the fornix, cingulum, and uncinate fasciculus (UF) is less well studied.ObjectiveTo assess MS damage to a hippocampal–thalamic–prefrontal network and the relative contributions of its components to specific cognitive domains.MethodsWe calculated diffusion tensor fractional anisotropy (FA) in the fornix, cingulum … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
44
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(55 citation statements)
references
References 46 publications
9
44
2
Order By: Relevance
“…The damage induced by MS in the hippocampal-thalamic-prefrontal network and its contributions to depression and specific cognitive domains was assessed by Kern et al [26]. These authors found that compared to healthy controls, patients with RRMS had a reduced mean FA of the UF, fornix and cingulum which agreed with our findings.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The damage induced by MS in the hippocampal-thalamic-prefrontal network and its contributions to depression and specific cognitive domains was assessed by Kern et al [26]. These authors found that compared to healthy controls, patients with RRMS had a reduced mean FA of the UF, fornix and cingulum which agreed with our findings.…”
Section: Discussionsupporting
confidence: 89%
“…The fornix has been associated with differences in MS on verbal memory tests, including CVLT-II [23,24] and BVRT [25]. A link between the FA of the fornix and verbal memory performance was identified in a previous study [26], but this relationship was not independent of thalamic volume. Additionally, the thalamic volume and FA of the fornix were strongly associated, which has been previously shown [25].…”
Section: Discussionmentioning
confidence: 84%
“…Increased TSPO levels in thalamus, hippocampus, and NAWM were associated with impaired SDMT function, a measure of information processing speed, which is frequently affected in MS and, thus, commonly evaluated in clinical setting. Diffusion imaging data highlighted that hippocampal-thalamic-prefrontal disruption affects SDMT performance in RRMS 47 . An association between depression and hippocampal neuroinflammation, as measured 18 F-PBR11, has been recently reported in RRMS 39 .…”
Section: Discussionmentioning
confidence: 99%
“…113 A strong association of damage to strategically crucial deep gray matter nuclei such as thalamus or putamen with impaired cognitive processing has been demonstrated by multiple studies. 50,[114][115][116][117][118][119][120][121] Moreover, gray matter damage of the hippocampus which is especially relevant for memory performance has been revealed by various imaging techniques and was shown to be related to memory-related aspects of cognitive performance in MS.…”
Section: Deep Gray Matter Damagementioning
confidence: 99%